The mediating effect of good governance on the relationship between managerial roles and personal development: A structural equation modeling (SEM) approach - Juhary, Ali; Ilham, Sentosa (2008)
One of the challenges faced by public sector managers particularly is the problem of identifying and determining their roles, their personal development and how to effectively implement the concept of good governance in their organizations. Given a dynamic changing and continuing insight into public organizational effectiveness, public sector managers are rethinking how best they could accomplish their roles in order to attain their organization roles and objectives. This study examines the mediating roles of good governance in the relationship between managerial roles, development roles, strategic roles and personal development. In determining this relationship, a hypothetical model of the relationship among roles of public sector managers, good governance and personal development is developed. The results suggest that the managerial roles has more positive and significant influence on personal development than the development roles and strategic roles.Empirical study supports the institutional theory (Scott, 2001) in the hypothesized model. The empirical findings confirm that good governance has a significant and positive impact on the relationship between managerial roles and development roles to the personal development of public sector managers. This proves that the management system theory (Katz & Kahn, 1966) is supported whereby public sector manager roles served as an input, while good governance as a process and personal development as an output. Based on empirical findings, it is suggested that personal development should be referred as an ideal social behavior of public sector managers. Overall, the study supports the hypotheses that good governance plays a mediating role in the relationship between public sector manager roles and personal development. This is consistent with governance theory (Lynn, 2001). One particular contribution of this study is the development of structural equation model to determine the relationships between managerial roles, good governance and the personal development of public sector managers. In conclusion, an understanding of the constructs of managerial roles is a prerequisite for better insight on personal development. The study confirms public sector managers to implement good governance to improve their personal development paths. The findings are discussed in the context of public sector managers in local government in Indonesia.